Otoprotectants: From Research to Clinical Application - Le Prell, Colleen G. (Seminars in Hearing, 2019)
There is an urgent need for otoprotective drug agents. Prevention of noise-induced hearing loss continues to be a major challenge for military personnel and workers in a variety of industries despite the requirements that at-risk individuals use hearing protection devices such as ear plugs or ear muffs. Drug-induced hearing loss is also a major quality-of-life issue with many patients experiencing clinically significant hearing loss as a side effect of treatment with life-saving drug agents such as cisplatin and aminoglycoside antibiotics. There are no pharmaceutical agents approved by the United States Food and Drug Administration for the purpose of protecting the inner ear against damage, and preventing associated hearing loss (otoprotection). However, a variety of preclinical studies have suggested promise, with some supporting data from clinical trials now being available as well. Additional research within this promising area is urgently needed.
Keywords: otoprotection; ototoxicity; noise-induced hearing loss; drug-induced hearing loss